SUSTAINABILITY STUDIES OF THE EYVAN TUNNEL AND ITS ROADS IN ORDER TO IMPROVE THE ROAD - Zabihollah Tajbakhsh, Mostafa Sharif Zadeh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The Ilam-Eyvan road is currently most important connection route of Ilam province with the central regions and other neighboring provinces. The purpose of this paper is to study the stability of the Eyvan tunnel. Sustainability and instability assessment of underground Drillings and tunnels are the most important parameters in designing this structure. There are various methods for analyzing the sustainability of underground spaces that can be used to analyze the stability of underground spaces and determine their storage system. The most reliable way to analyze the stability of these spaces is to use a number of different methods for analysis so that these methods complement each other, deliver more reliable and optimal results. In the most general case, the tunnel is evaluated using empirical methods and also primary preservatives are predicted based on the initial analysis, and then analyzes are performed more accurately using analytical or numerical methods. In this study, FLAC3D software was used for modeling and analysis of the Eyvan tunnel. The results and diagrams with the software included changes in shape, principal tension and shear stresses in different sections of the drilled tunnel. On average, the result of calculations showed a concrete cover across the tunnel.